2005
DOI: 10.1007/s00421-005-1402-8
|View full text |Cite
|
Sign up to set email alerts
|

Sedative effects of the jasmine tea odor and (R)-(−)-linalool, one of its major odor components, on autonomic nerve activity and mood states

Abstract: We investigated the effects of the odor of jasmine tea on autonomic nerve activity and mood states in a total of 24 healthy volunteers. We used the odor of jasmine tea at the lowest concentration that could be detected by each subject but that did not elicit any psychological effects. R-R intervals and the POMS test were measured before and after inhalation of the odors for 5 min. Both jasmine tea and lavender odors at perceived similar intensity caused significant decreases in heart rate and significant incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(130 citation statements)
references
References 34 publications
7
119
0
4
Order By: Relevance
“…These results suggest that linalool had a dose-dependent sedative effect in neonatal chicks as observed for CEO (8.6 and 86 mg) and diazepam (17.5 mg). It has been reported that i.p administration or inhalation of linalool had a sedative effect in rodents and humans (Kuroda et al 2005;Linck et al 2009), however, until now, there are no reports with similar behavioural effects in avian species.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that linalool had a dose-dependent sedative effect in neonatal chicks as observed for CEO (8.6 and 86 mg) and diazepam (17.5 mg). It has been reported that i.p administration or inhalation of linalool had a sedative effect in rodents and humans (Kuroda et al 2005;Linck et al 2009), however, until now, there are no reports with similar behavioural effects in avian species.…”
Section: Discussionmentioning
confidence: 99%
“…Power spectral analysis has been used to detect changes in autonomic nervous activity in response to the intake of foods or the inhalation of odors in humans. [14][15][16][17] Details of the power spectral analysis procedure have been fully described by Moritani et al 18,19) A power spectral analysis by fast Fourier transformation was performed on consecutive 256-s time series of the R-R interval data obtained during the test. To evaluate the autonomic nervous system activity of each subject in the present study, we analyzed both low-frequency (LFC, 0.035-0.15 Hz) and high-frequency (HFC, 0.15-0.5 Hz) components, the latter being the respiration-linked component.…”
Section: Methodsmentioning
confidence: 99%
“…31 As a global measure of affective state, a total mood disturbance (TMD) score was also calculated, with higher scores indicating more mood disturbance, by adding the Tscores on the six subscales; vigor was negatively weighted. 17,32 Referring to a study by Kuroda and colleagues 33 and the authors' recent aroma research, 26 to investigate the effect of yuzu aroma on mood states, changes in the POMS scores of the yuzu and control trials were compared before and 30 minutes after the aroma stimulation.…”
Section: Assessment Of Emotional Symptomsmentioning
confidence: 99%